Characteristics of and Experience Among People Who Use Take-Home Naloxone in Skåne County, Sweden - Troberg, Katja; Isendahl, Pernilla; Blomé, Marianne Alanko; Dahlman, Disa; Håkansson, Anders (Frontiers in Public Health, 2022)
Background Opioid overdose related injury or death can be prevented by bystander naloxone administration. For naloxone to be present when and where overdoses occur, opioid prevention education and naloxone distribution (OPEND) must be established on a broad level. This is the 30-month follow-up of the first multi-site naloxone project in Sweden, implemented at 31 sites in the County of Skåne 2018. Aim To address participant characteristics and factors associated with returning for naloxone refill and with having used naloxone for overdose reversal. An additional aim was to describe self-reported reasons for naloxone refill and overdose experiences. Methods Data were collected during June 2018—December 2020 through questionnaires at baseline and upon naloxone refill of the initial and subsequent naloxone kit. Descriptive statistics was used to address participant characteristics, those returning for naloxone refill and reporting overdose reversal. Chi-2 test was used for variable comparison between groups. Factors associated with overdose reversals were examined by logistic regression analysis. Reasons for naloxone refill, overdose situation and management were presented descriptively. Results Among 1,079 study participants, 22% (n = 235) returned for naloxone refill, of which 60% (n = 140) reported a total of 229 overdose reversals. Reversals were more likely to be reported by participants trained at needle exchange programs (NEPs) [adjusted odds ratio (AOR) = 5.18, 95% Confidence interval (CI) = 3.38–7.95)], with previous experience of own (AOR = 1.63, 95% CI = 1.03–2.58) or witnessed (AOR = 2.12, 95% CI = 1.05–4.29) overdose, or who had used sedatives during the last 30 days before initial training (AOR = 1.56, 95% CI = 1.04–2.33). A majority of overdoses reportedly occurred in private settings (62%), where the victim was a friend (35%) or acquaintance (31%) of the rescuer. Conclusion Participants with own risk factors associated with overdose (e.g., injection use, concomitant use of benzodiazepines and previous experience of own overdose) were more likely to report administering naloxone for overdose reversal. Overdose management knowledge was high. The findings indicate that implementation of multi-site OPEND reaches individuals at particularly high risk of own overdose in settings with limited previous harm reduction strategies and favors a further scaling up of naloxone programs in similar settings.